Beta‐blockers in hospitalised patients with cirrhosis and ascites: mortality and factors determining discontinuation and reinitiation. Issue 1 (9th October 2017) - Bhutta, A. Q.; Garcia‐Tsao, G.; Reddy, K. R.; Tandon, P.; Wong, F.; O'Leary, J. G.; Acharya, C.; Banerjee, D.; Abraldes, J. G.; Jones, T. M.; Shaw, J.; Deng, Y.; et al.
Summary: Background: It has been suggested that beta‐blockers may increase mortality in patients with cirrhosis and refractory ascites but the effect of beta‐blockers discontinuation or reinitiation has not been examined. Aims: To compare, in hospitalised patients with cirrhosis and ascites, the effect of BB on survival and to examine the effect/predictors of beta‐blockers discontinuation and reinitiation. Methods: Sub‐analysis of NACSELD (North American consortium for the study of end‐stage liver disease, database containing prospective data on hospitalised patients with cirrhosis) data from 7 centres enrolling >100 patients with ascites. Data on BB discontinuation and reinitiation were collected by chart review. Results: Seven hundred and sixteen patients, 307 (43%) on beta‐blockers at admission and 366 (51%) with refractory ascites, were followed to death or hospital discharge. Beta‐blocker use was associated with a lower white blood cell count at admission. Beta‐blocker use in hospitalised patients with ascites was not associated with a higher mortality, even in those with refractory ascites. No significant changes in mean arterial pressure (MAP) were observed between groups. Discontinuation of beta‐blockers (49%) was driven by low MAP, infection and acute kidney injury at time of discontinuation but was not associated with a higher mortality. Beta‐blocker reinitiation occurred in 40% prior to discharge and was mainly driven by an increase in MAP. Conclusions: Beta‐blocker use is safe in patients with cirrhosis and ascites (including those with refractory ascites) provided beta‐blockers are discontinued in the presence of a low MAP and reinitiated once MAP reincreases. A potentially beneficial anti‐inflammatory effect of beta‐blockers is suggested. Abstract : Linked Content This article is linked to Ferguson and Armstrong paper. To view this article visithttps://doi.org/10.1111/apt.14402 .